Forget EPSSs: How You Can Marshal Mobile Geographic Information Systems (GISs) and Spatial Awareness for Performance Improvement. Issue 10 (November 2016) - Carl, Diana R.
Abstract : Mobile geolocation applications identify global coordinates of mobile devices and can be enriched with performance‐context data. This technology has potential to integrate job aids, learning bursts, and parts of manuals with work tools (such as checklists) at the point of performance to better support individual and team performance. Emerging uses of mobile geolocation allow human performance technologists to move from generic electronic performance support systems (EPSSs) to spatial support systems. These increase the potential for performers to access more context‐aware information at the time and space in which the actions occur. Mobile geolocation can also automatically send data about the performance to enterprise databases so that actions taken and the use of training or job aids at the point of performance can be tracked. This article explores how mobile geolocation functionality can be orchestrated to support performance, enrich enterprise databases, and aid human performance technologists.